Vector Sum Analysis Method of Loess Slope Stability under Rising Groundwater Level Conditions. (16th October 2019) - Xue, Haibin; Dang, Faning; Li, Yanlong; Yin, Xiaotao; Lei, Man
Abstract : The stability analysis of loess slopes with a rising groundwater level is a problem that integrates unsaturated and transient seepage, stress analysis, and stability prediction. For this purpose, a sequentially coupled method of seepage-softening-stability was used. First, seepage analysis of a loess slope with a rising groundwater level was conducted according to unsaturated and transient seepage analysis theory. Second, the spatial distribution of the deformation and strength parameters of the soil, both of which were based on the calculated results of the seepage analysis, were adjusted according to the water-induced structural deterioration equation. Third, the vector sum analysis method of loess slope stability, which was based on the temporal-spatial distribution laws of effective unit weight, elastic modulus, Poisson's ratio, cohesion, internal friction angle, and seepage force, was performed by the body force method. To verify the proposed method, the limit equilibrium method of loess slope stability was conducted by the surface force method. Finally, the progressive failure process of a loess slope with a rising groundwater level on the White Deer Plain was presented as an example. A comparison analysis of the calculated results of the two methods revealed that the proposed method was reasonable and reliable.